Correlation between psychological fatigue and muscle fatigue associated with prolonged standing - Isa, Halim (Universiti Malaysia Perlis, 2011)
Objectives: The objectives of this study were to determine the psychological fatigue and analyze muscle activity of production workers who are performing processes jobs in prolonged standing. Methods: The psychological fatigue has been assessed through questionnaire surveys. On the other hand, the muscle fatigue has been analyzed using a surface electromyography (sEMG) instrument. The lower extremities muscles including erector spinae, tibialis anterior, and gastrocnemius were concurrently analyzed for 5 hours and 45 minutes of continuous standing. Twenty male production workers from a metal stamping company participated as subjects in this study. The subjects were required to undergo questionnaire surveys and sEMG measurement. Results: Results of questionnaire surveys found that all subjects experienced psychological fatigue while performing processes jobs in prolonged standing. Similarly, muscle fatigue has been identified through sEMG measurement. Based on the non-parametric statistical test using the Spearman’s Rank Order Correlation, the left erector spinae obtained a moderate positive correlation and statistically significant (rs = 0.552, p = 0.012 < 0.05) between the results of questionnaire surveys and sEMG measurement. Conclusion: Based on the results, the authors concluded that prolonged standing was the contributor to psychological fatigue and muscle fatigue among the production workers.